FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA DI SEKTOR INDUSTRI DAN PERDAGANGAN DI KABUPATEN/KOTA DI SUMATERA BARAT - Muhammad Aidil Idham; Alpon Satrianto (Universitas Negeri Padang, 2018)
This study aims to determine and analyze the factors that influence labor in the industrial and trade sectors in the province of West Sumatra. The type of data in this study is panel data from 19 districts / cities in West Sumatra. In analyzing sequential data for 2011 to 2015, the analytical method is the Regression Model Panel, the Classic Assumption Test and the t Test. Based on the results of testing the economic growth of West Sumatra, this is significant for workers in West Sumatra, while education and health have no significant effect on workers in West Sumatra. Positive economic strengthening of labor absorption Increased economic growth. While education and health do not have the cost to work.. Keywords: economic growth, education, health and labor